The Effect of Aloevera Mouthwash in Reducing Periodontal Disease among Secondary School Students in Duhok, Kurdistan Region, Iraq: A Quasi-Experimental Study - Nasreen Hamonari; Samim A.AL-Dabbagh; Anees Mahmud Mudhir (Institute of Medico-legal Publications Pvt Ltd, 2021)
As the prevalence of periodontal diseases increases and antibiotic resistance develops, there is a need for alternative methods of treatment, safe, reliable and economical. Worldwide, dentistry has recently shown a change in approach to the use of such modalities to treat many inflammatory oral diseases. Aloe vera is a medicinal herb with many advantages and has recently gained considerable importance in clinical research. Aim: The aim of this study is to determine the effect of using Aloe vera mouthwashes on improving periodontal health among secondary school students in in Duhok, Kurdistan Region, Iraq.Materials and Methods: A quasi experimental study conducted on 289 systemically healthy participants with moderate and severe gingivitis (132 females and 157 males) aged 14-20 years randomly selected from eight secondary schools using multistage random sampling in Duhok city from December 2018 to May 2019. The periodontal status was assessed by using the Gingival Index and Plaque Index before and 4 weeks after using Aloevera mouthwash. Results: there was a significant decrease in the means of plaque and gingival indices after using Aloe vera mouthwash in the whole sample (p < 0.001), and among each gender (p < 0.001). Conclusion: The finding of this study showed that Aloe vera could prove to be effective mouthwash due to its ability to reduce periodontal indices. Therefore, Aloe vera can be used as an alternative product for the prevention and treatment of gingivitis.